P223 NIV....A Kiss of Life. (19th November 2012) - Rauf, F; Qureshi, I; Ali, A
Abstract : Background: Non-invasive ventilation (NIV) can be a lifesaving intervention and this is recommended treatment for acute hypercapnoeic respiratory failure. However it is thought to be a distressing intervention by some patients & families. We performed a survey of patient's perception of acute ward based NIV and its effect on their symptoms. Method: With a brief questionnaire we enquired patients how they felt when NIV was commenced and positive or negative effects of NIV on various symptoms. 20 consecutive patients who were admitted for acute NIV from February to April 2012 were included. A record was also made about the place where NIV was initially instituted. Findings: 75% patients received NIV for COPD exacerbations. 65% patients were NIV naive. 90% of patients recalled initiation of NIV. 55% of treatments were started in emergency department (ED). 63% of ED patients and 77% of ward patients recalled that they were explained about the treatment before starting. 90% patients recognised NIV as a lifesaving intervention and 90% wanted to receive this again if needed acutely and 65% would accept domiciliary NIV if offered. 85% reported improvement in breathing, 40% felt reduction in tiredness & headaches and 5% felt improvement in exercise tolerance. However 5% patients felt that NIV has actually worsened their breathing, another 5% felt that there was no improvement in symptoms at all. The commonest negative feelings were claustrophobia (45%) followed by fatigue (40%), sleeplessness (35%), inability to breathe (30%) & feeling panicked (25%). Some interesting comments were, "Like being given a kiss of life" "Lifesaving piece of equipment which is not a comfort ride but it is necessary" "I know this is horrible but I shall always say go for it mate". Interpretation: Almost all patients will feel distressing symptoms including agitation and claustrophobia in the beginning of treatment but these feelings settle very quickly and majority of them feel improvement in their key respiratory symptoms. Contrary to common perception majority will be happy to have treatment again. Patients felt that a detailed explanation and counselling before starting NIV improves compliance and successful outcome from NIV.